Antibacterial Efficacy of Rotary and Reciprocating Instrumentation Techniques - Anja Sesar; Ana Budimir; Ivica Anić; Gabrijela Kapetanović Petričević; Ivona Bago (University of Zagreb. School of Dental Medicine, 2024)
Objectives: To clinically evaluate the effectiveness of rotary (ProTaper Next [PTN]) and reciprocating (Wave One Gold [WOG]) instrumentation techniques in eliminating bacteria from the root canals of teeth with apical periodontitis during a single-visit root canal treatment. Materials and methods: Forty patients were randomly assigned to the WOG or PTN instrumentation techniques groups. A singlevisit root canal treatment was performed on all the patients. In both groups, root canals were irrigated with 10 ml of sodium hypochlorite (NaOCl) and the final irrigation protocol was applied. Microbiological samples from the root canal were collected initially (Sample 1), after chemo-mechanical instrumentation (Sample 2), and after the final irrigation protocol (Sample 3). Quantification of bacteria at each stage of root canal treatment was performed using the culture method (colony-forming units [CFUs]), and bacterial species were identified using MALDI-TOF mass spectrometry. Results: There were 50 aerobic and anaerobic bacterial species identified. Chemo-mechanical root canal treatment with both instrumentation techniques and the final irrigation protocol significantly reduced the number of CFUs (p<0.001). There were no statistically significant differences in antibacterial efficacy between WOG and PTN groups (p>0.05). Conclusion: Although both root canal instrumentation techniques were highly effective in removing bacteria from the necrotic canals of teeth with chronic apical periodontitis, no complete eradication of bacteria was found in any sample.